Governance of Leadership Materials and Communication in Regional Leader Speech Preparation: A Qualitative Study at a Provincial Leadership Administration Bureau - Julfikar C. Pasambuna; Steven V. Tarore; Laurens L. Bulo (JR Education, 2026)
This article examines the governance of leadership materials and communication in the preparation of regional leader speeches at a provincial leadership administration bureau. Leadership speeches are not merely ceremonial texts; they are instruments of public administration through which government priorities, development achievements, policy directions, and public values are communicated. The study uses a descriptive qualitative approach because the phenomenon is embedded in administrative routines, inter-unit coordination, data provision, staff competence, and agenda dynamics. Data were collected through observation, in-depth interviews with officials and staff involved in speech preparation, and documentation of schedules, organizational structures, speech materials, and supporting administrative records. The analysis is organized around five indicators: activity coordination, schedule planning, data sources for speech materials, composing apparatus, and contingency of leader attendance. The findings show that the speech preparation process has been supported by a formal organizational structure and highly committed personnel, yet it has not functioned optimally as an integrated governance system. Coordination still relies on informal communication channels, schedule changes frequently occur at short notice, data from regional apparatus organizations are often late or not standardized, writing competence is uneven, and changes in leader attendance often result in unused or repeatedly revised materials. The discussion shows that effective leadership communication requires the integration of bureaucratic order, performance orientation, public service values, and communication quality. The article recommends strengthening standard operating procedures, developing a real-time agenda and material management system, institutionalizing data submission standards, and improving civil servant competence in public communication and speechwriting.